Development of a Novel Orthotopic Primary Human Chordoma Xenograft Model: A Relevant Support for Future Research on Chordoma. Issue 3 (15th November 2019) - Salle, Henri; Pocard, Marc; Lehmann-Che, Jacqueline; Bourthoumieu, Sylvie; Labrousse, François; Pimpie, Cynthia; Lemnos, Leslie; Guichard, Jean-Pierre; Froelich, Sebastien; Adle-Biassette, Homa
Abstract: Chordomas are slow-growing rare malignant neoplasms. The aim of this study was to establish a primary model of chordoma in the lumbosacral orthotopic area, to compare the growth rate to the subcutaneous site, and to show that this new graft site optimizes tumor growth and bony invasion. Eleven chordoma samples were transplanted subcutaneously in the flank and/or in contact with the lumbosacral region and grown into nude mice. Engraftment rate was significantly more successful in the lumbosacral environment compared with the flank at P0. Two xenografts from 2 patients showed bone invasion. One tumor was maintained through multiple rounds of serial transplantation, creating a model for study. Histological and immunostaining analysis confirmed that tumor grafts recapitulated the primary tumor from which they were derived, consisting of a myxoid chordoma expressing brachyury, cytokeratin AE1, EMA, and VEGF. Clear destruction of the bone by the tumor cells could be demonstrated. Molecular studies revealed PIK3CA and PTEN mutations involved in PI3K signaling pathway and most of the frequently reported chromosomal alterations. We present a novel orthotopic primary xenograft model of chordoma implanted for the first time in the lumbosacral area showing bone invasion, PIK3CA, and PTEN mutations that will facilitate preclinical studies.